Digital Mindset Deficit in MSMEs Leadership: A Grounded Theory Study of Pottery Enterprises in Lombok - Urfina, Yasyifa Dian; Syiam, Nazilatus; Hadi, Sulhan; Candra , Candra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The digital economy has significantly transformed the global business environment, making digital technology a critical determinant of business competitiveness and sustainability. Despite their strategic importance, many small and medium enterprises (SMEs) face significant challenges in implementing digital transformation initiatives. This study investigates leadership-related barriers to digital transformation among Pottery SMEs in Lombok, Indonesia, with a particular focus on how deficiencies in digital mindsets emerge and shape managerial decision-making. Adopting a grounded theory approach, qualitative data were collected through in-depth interviews and participant observation involving SME owners and managers. Data analysis was conducted through systematic open, axial, and selective coding procedures, supported by NVivo software, to generate substantive theory grounded in empirical findings. The results reveal a persistent gap between awareness of digital technologies and their effective integration into daily business practices. Cognitive limitations, uncertainty, and sociocultural norms influence leaders' perceptions of digital technologies and limit their confidence in adopting digital solutions. Consequently, decision-making regarding digital initiatives remains largely intuitive and reactive rather than strategic and forward-looking, reflecting limited digital leadership capabilities. Despite this, SME leaders expressed a generally optimistic view of digital transformation, particularly regarding market expansion and business sustainability. They emphasized the importance of practical training, ongoing mentoring, and accessible digital infrastructure to facilitate digital adoption. This study provides context-specific insights into the barriers to digital mindsets in SME leadership and underscores that successful digital transformation requires not only technological readiness but also cognitive readiness and supportive institutional and socio-cultural conditions.